2015
DOI: 10.1080/13811118.2015.1004490
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors of Suicidal Ideation and Attempt among Adolescents with Different Types of School Bullying Involvement

Abstract: Suicide has been found to be prevalent among adolescents involved in bullying; however, there has been a lack of research examining whether the risk and protective factors of suicidal ideation and attempt are different among adolescents with different types of bullying involvement. The aims of this study were to examine the risk and protective factors of suicidal ideation and attempt among adolescents with different experiences of bullying involvement, victimization, and perpetration. A total of 4,533 adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
4
21
4
1
Order By: Relevance
“…Although Volk et al proposed that bullying perpetration may be the result of an evolutionarily adaption for somatic resources, mates, and dominance [7], some researchers argued that both pure bullying perpetrators and perpetrator-victims have higher risks to develop mental health problems [2,8]. A previous study also reported that both pure perpetrators and perpetrator-victims were more likely to report suicidal ideation and attempt than the neutral group [9]. Therefore, school bullying is an important topic and requires early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Although Volk et al proposed that bullying perpetration may be the result of an evolutionarily adaption for somatic resources, mates, and dominance [7], some researchers argued that both pure bullying perpetrators and perpetrator-victims have higher risks to develop mental health problems [2,8]. A previous study also reported that both pure perpetrators and perpetrator-victims were more likely to report suicidal ideation and attempt than the neutral group [9]. Therefore, school bullying is an important topic and requires early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research on suicide has focused on the identification of factors that increase the risk of this behaviour [ 13 ]. In contrast, we know very little about the factors that decrease the likelihood of suicidal behaviour among those exposed to known risk factors such as bullying victimisation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because bullying and cyberbullying victimisation are known mental health risk factors among adolescents [ 8 , 14 ], it is important to consider the vulnerability of this age group and any protective factors that might be associated with psychological adjustment. In this sense, protective factors lessen the likelihood of bullying victimisation and mediate or moderate the effects of risk factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Violence victimization among adolescents is linked to a wide range of psychiatric symptoms, such as depression, anxiety, and suicidality [8,9,10,11]. In particular, experiencing prior victimization at an early age has been found to predict an increased risk for depression or deviance later in life [5,12,13].…”
Section: Introductionmentioning
confidence: 99%